The impacts of COVID-19 pandemic and lockdown on caregivers of family members with mental health issues : the untold story - Afifah Idris,; Noremy Md. Akhir, (Penerbit Universiti Kebangsaan Malaysia, 2022)
COVID-19 was officially declared as a global pandemic in March 2020, confirming the disease’s threat to human health and well-being. Since then, the world is dealing not only with the infections, but also with the negative effects on mental health. Countries have closed their borders in the war against the pandemic, travel between and within the country has been restricted, and life has come to a halt in many parts of the world. The government-imposed limitations in all pandemic-affected nations, including Malaysia, have had an indirect and harmful impact towards the caregivers of family members with depression. This has been the subject of several studies by the researchers. However, there was paucity of information regarding this issue in the Malaysian context. Hence, this article aims to explore the challenges faced by the caregivers before the pandemic, psychological impacts of COVID-19 towards the community and caregivers of family members with mental health issues, as well as the needs to help the latter during the pandemic. To the researcher’s knowledge, no such study has been performed in the Malaysian context. Thus, more research on this topic is required in the future. This kind of research gives light to the untold story from the caregiver’s point of view. Recommendations for future research and implications for social work practice are discussed.